Essays in econometrics, Volume 1, Spectral analysis, seasonality, nonlinearity, methodology, and forecasting collected papers of Clive W.J. Granger - Granger, C. W. J. 1934-2009 (Econometric Society monographs, 2001)
This book, and its companion volume in the Econometric Society Monographs series (ESM number 33), present a collection of papers by Clive W. J. Granger. His contributions to economics and econometrics, many of them seminal, span more than four decades and touch on all aspects of time series analysis. The papers assembled in this volume explore topics in spectral analysis, seasonality, nonlinearity, methodology, and forecasting. Those in the companion volume investigate themes in causality, integration and cointegration, and long memory. The two volumes contain the original articles as well as an introduction written by the editors